The Phenomenon of Self-Harm Among Indonesian Youth and Its Implications in Guidance and Counseling - Desma, Fina Putri; Yendi, Frischa Meivilona (Universitas Negeri Padang, 2024)
The background of this study is the phenomenon of self-harm among teenagers today which is done to vent emotions because there are various problems that cannot be resolved properly. Problems that occur if not handled properly and create emotional stress can encourage teenagers to do self-harm. This study aims to describe the phenomenon of self-harm that occurs among teenagers in Indonesia and the causes of self-harm. This study uses a qualitative approach method with a literature study method. The data sources for this study are literature such as scientific articles and books. The data analysis technique used is a narrative review. The results of the study found that adolescence is a vulnerable period for self-harm due to various factors and problems that cannot be resolved properly such as stress, depression, anxiety and inability to control emotions. Related to this behavior, guidance and counseling services can be provided to reduce self-harm behavior such as information services, individual counseling services and group counseling services.